Közép-európai új városok az átmenetben (Szociológiai Szemle, 2024)
The paper studies the processes of transition taking place in the Central European new towns, the place occupied by the new towns in the Central European urban system, the macro-social, political, economic and ideological processes and urbanistic doctrines, the urban roles determining their emergence and development. During the course of the historical analysis of the major actors developing the new towns light is shed upon the participation of the state, the most important representatives of the economy including big companies, local governments and the population, upon the circle of major actors determining urban development today, and upon the specificities of the societies of new towns, including the spatial order of local social structure and the problem of segregation. The special features of foundations and associations as mechanisms integrating civil society are also studied. The results published in the paper are parts of an international comparative study entitled ’’European New Towns at the End of the Twentieth Century”. The background of the analysis is offered by concrete case-studies based on interviews in-depth and a comparison of social statistics of the special features of new and old towns built upon the data base of the decennial census.